Inflation and Activity : Two Explorations and their Monetary Policy Implications - Blanchard, Olivier (IMF Working Papers; Working Paper, 2015)
We explore two issues triggered by the crisis. First, in most advanced countries, output remains far below the pre-recession trend, suggesting hysteresis. Second, while inflation has decreased, it has decreased less than anticipated, suggesting a breakdown of the relation between inflation and activity. To examine the first, we look at 122 recessions over the past 50 years in 23 countries. We find that a high proportion of them have been followed by lower output or even lower growth. To examine the second, we estimate a Phillips curve relation over the past 50 years for 20 countries. We find that the effect of unemployment on inflation, for given expected inflation, decreased until the early 1990s, but has remained roughly stable since then. We draw implications of our findings for monetary policy.